Identification of Feasibility of Canned Based Foods Image Processing Techniques Using Thresholding - Ilhamsyah Muhammad Nurdin; Abdul Fadlil (Universitas Ahmad Dahlan, 2021)
Eye sight is sometimes deceptive, especially in determining the quality of a canned food, so it is necessary to use technology that resembles human visual observation, namely in the form of an application. The process to detect the quality of canned food uses image processing methods, especially thresholding, which is then designed so that the application is able to determine the quality of canned food with the help of the MATLAB GUI which detects and then sends it from making the MATLAB GUI on the Laptop to Android using FTP (File Transfer Protocol). At the end of the process, it is marked with known good and bad quality of canned food with an android application that has been specially designed with an accuracy level of 84% with a thresholding value of 70.